2014
DOI: 10.3109/15412555.2014.908830
|View full text |Cite
|
Sign up to set email alerts
|

Bi-level Positive Airway Pressure (BiPAP) with Standard Exhalation Valve Does Not Improve Maximum Exercise Capacity in Patients with COPD

Abstract: Use of BiPAP with a standard exhalation valve during exercise increases VT and VE at the expense of augmenting VCO2 and dyspnea, which in turns reduces WLpeak in COPD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
2
8
1
Order By: Relevance
“…Nonetheless, information regarding the effect of NIMV on maximum exercise workload (WLmax) is limited. Moga et al (18) reported a decrease in WLmax with the application of Bi-level positive airway pressure (BiPAP) during exercise, and concluded that the BiPAP's single limb tubing for inspiration and expiration resulted in carbon dioxide (CO 2 ) rebreathing and contributed to the reduction in WLmax. The occurrence of CO 2 rebreathing with BiPAP has been reported in both laboratory (19,20) and clinical (19,21) studies.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, information regarding the effect of NIMV on maximum exercise workload (WLmax) is limited. Moga et al (18) reported a decrease in WLmax with the application of Bi-level positive airway pressure (BiPAP) during exercise, and concluded that the BiPAP's single limb tubing for inspiration and expiration resulted in carbon dioxide (CO 2 ) rebreathing and contributed to the reduction in WLmax. The occurrence of CO 2 rebreathing with BiPAP has been reported in both laboratory (19,20) and clinical (19,21) studies.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, investigating the effects of a single-limb circuit with a Silentflow Exhalation valve (Weinmann, Hamburg, Germany) to deliver ventilatory assistance (IPAP: 29.5±4.1 cmH 2 O, EPAP: 4.38±0.82 cmH 2 O) during exercise in COPD with hypercapnia,16,17 there were controversial outcomes on the alleviation of dyspnea. Moreover, in studies by Moga et al19 and Highcock et al,20 they found that BiPAP with Whisper Swivel II did not improve exercise capacity. These findings, in combination with the result found by Ferguson and Gilmartin21 that significant CO 2 rebreathing could occur at low expiratory pressure levels (≤4 cmH 2 O) on single-limb circuit with Whisper Swivel Valve or other fixed-resistance exhalation devices, suggested that CO 2 may not be adequately cleared with the fixed-resistance exhalation valve both at rest and during exercise and that this blunted the efficacy of NIV.…”
Section: Discussionmentioning
confidence: 93%
“…In these studies, one of the obvious methodological issues existed with respect to the selection of exhalation valve connected to the single-limb circuit. Evidence from Moga et al19 and Highcock et al20 indicated that NIV with a single-limb circuit with Whisper Swivel II expiratory valve (Respironics Inc., Murrysville, PA, USA) assisting exercise did not improve exercise capacity in COPD patients. Also, as previously reported by Ferguson and Gilmartin,21 the use of Whisper Swivel II expiratory valve during bi-level positive airway pressure (BiPAP) ventilatory assistance causes CO 2 rebreathing, which can blunt any effect of BiPAP on partial pressure of CO 2 (PaCO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its complexity and the many parameters influencing its use, NIV during exercise is a much-debated topic with divergent results, particularly when used over a course of PR. Indeed, previous acute and physiological studies has mostly demonstrated a significant positive effect of NIV on exercise capacity [11,12,[28][29][30] or no positive effects [31,32], while long-term studies remain inconclusive [7,18,33]. In this context, the detrimental effect of NIV on endurance exercise capacity found in the present study was quite unexpected and it is therefore difficult to differentiate between a real worsening in endurance exercise capacity or a lack of improvement (there is also a possibility of a type 1 statistical error).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other factors such as the low pressure support used [3,4], NIV-induced hypercapnia [31,35] or the patient's selection (i.e., without chronic hypercapnic respiratory failure (CHRF)) may also explain the lack of improvement in Tlim. Indeed, higher inspiratory support may have led to a positive effect of NIV as suggested by Gloeckl et al who found a significant improvement in endurance capacity with high-pressure NIV during exercise in patients already undergoing long-term NIV for CHRF [36].…”
Section: Discussionmentioning
confidence: 99%